ANALISIS PROGRAM PEMBERDAYAAN MASYARAKAT PADA USAHA MENENGAH KECIL DAN MIKRO (UMKM) (Studi di UMKM Pengrajin Batik Kampoeng Jetis dan Pengrajin Koperasi Intako Tanggulangin Sidoarjo) - Nawangsari, Ertien Rining (JPSI (Journal of Public Sector Innovations), 2016)
Sidoarjo is a SMEs city that has a number of industrial quite a lot, one of which is a small industry of batik artisans that located in Kampung Batik Jetis and Intako Cooperative Craftsmen in Tanggulangin, Sidoarjo. How is the empowerment program that supports the development of batik craftsmen and intako craftsmen in Sidoarjo? And what are the factors inhibiting and supporting batik craftsmen and intako craftsmen?; Empowerment to those carried out by the Department of Cooperatives, SMEs, Industry, Trade, and Energy and Mineral Resources Sidoarjo conducted with various efforts, namely (1) facilitation of capital, (2) support the ease of obtaining raw materials and support facilities in the production process, (3) education and training to improve managerial capability and production, and other types of education and training that can support the empowerment of Micro, Small and Medium Enterprises, (4) involvement in trade fairs to expand market access, (5) facilitation of IPR. Four of five attempts have been made and the results still needs to be improved. The existence of barriers and support needs to be a concern for local governments to increase the empowerment of MSME